Pendampingan Pelatihan Penulisan Karya Tulis Ilmiah (KTI) di SMP Islam Nahdlatul Ulama Galis Bangkalan - Munib, Munib; Farida, Siti; Badtuttamam, Badtuttamam; Faddol, Moh.; Abdullah, Abdullah; Zainuddin, Zainuddin (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The increasingly advanced era has driven many changes in society, including among students at NU Galis Middle School in Bangkalan, Indonesia. One significant change is the widespread use of social media. Unwittingly, social media use can influence the learning outcomes of students. This mentoring program aims to investigate the influence of social media on the learning outcomes of students at NU Galis Middle School in Bangkalan. The Scientific Paper Writing (KTI) training program is for students at NU Galis Middle School in Bangkalan who are still in the learning process. In this study, the researcher will use a qualitative research approach. Qualitative research produces descriptive data in the form of words or writings from the participants observed. The results of this training demonstrate a significant relationship between writing creativity and the learning outcomes of students at NU Galis Middle School in Bangkalan. This indicates that the higher the intensity of writing, the higher the students' learning outcomes. The implication of this mentoring program is the importance of providing motivation and guidance to students in writing to improve the quality of their education.